Signatures of Gait Movement Variability in CKD Patients Scheduled for Hemodialysis Indicate Pathological Performance Before and After Hemodialysis: A Prospective, Observational Study - Zemp, Damiano D.; Giannini, Olivier; Quadri, Pierluigi; Rabuffetti, Marco; Tettamanti, Mauro; de Bruin, Eling D. (Frontiers in Medicine, 2021)
Background: The frailty status of hemodialysis patients is well-known, but the role of the therapy in the frailty process is not yet clear. Nowadays gait analysis in nephrology is neglected, although gait performance is known to be related to frailty and kidney function. We hypothesized that gait quality and physical activity level is already affected before, and does not change because of the start of hemodialysis. Methods: Fourteen patients (72.3 ± 5.7 years old) in a pre-dialysis program underwent an instrumental gait analysis and their physical activity was monitored for a week. This protocol was repeated 3, 6, 12, and 24 months after the first hemodialysis session. Results: At baseline, our sample showed a conservative gait with pathologic gait variability, high dual-task cost, and a sedentary lifestyle. No statistically significant change was found in any parameter in the analyzed period, but there was a tendency toward an improvement of gait quality and physical activity in the first year of treatment, and a decline in the second year. Conclusion: Elderly patients in the pre-dialysis stage show a conservative gait, however variability was in a pathological range and did not change post-hemodialysis. This hints toward changes in the central nervous system due to the kidney disease. This finding suggests the importance of gait analysis in the early stages of renal disease in the diagnosis of changes in the nervous system due to kidney failure that affect gait. Early detection of these changes would potentially allow a prevention program tailored to this population to be developed.